1996
DOI: 10.1002/chem.19960020614
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Transformations with Configurationally Labile α‐Phenylselenoalkyllithium Compounds

Abstract: Complexation of the configurationally labile cl-phenylselenoalkyllithium compound 8 with 1,2-bisdirncthylarninocyclohexane 15 Icd to two diastereomeric comadded more rapidly to benzaldehyde than the uncomplexed organolithiurn compound 8. Trapping of complexes 13 and 14 by bcnraldehyde wa5 chown to occur more rapidly than their equilibration. This corresponds to non-Curtin-Hammett kinetics, in which enantiorneric enrichment in the products reflects the equilibrium rdtio of the complexes 13and 14.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 51 publications
0
12
0
3
Order By: Relevance
“…In these direct preparation methods, the acyllithium species is generated in the presence of an electrophile (Scheme 4). [27] Optically pure or enriched lithium compounds can be prepared from the corresponding a-substituted organostannane compounds such as 21 [28] or with the aid of the enantioselective deprotonation developed by Hoppes group [23a] using (À)-sparteine as a chiral inductor (Scheme 5). [23] The chiral compounds first prepared were functionalized in the position a to oxygen.…”
Section: Polyfunctional Organolithium Reagentsmentioning
confidence: 99%
“…In these direct preparation methods, the acyllithium species is generated in the presence of an electrophile (Scheme 4). [27] Optically pure or enriched lithium compounds can be prepared from the corresponding a-substituted organostannane compounds such as 21 [28] or with the aid of the enantioselective deprotonation developed by Hoppes group [23a] using (À)-sparteine as a chiral inductor (Scheme 5). [23] The chiral compounds first prepared were functionalized in the position a to oxygen.…”
Section: Polyfunctional Organolithium Reagentsmentioning
confidence: 99%
“…[1,14] However, effective use of noncovalently linked chiral controllers in homogeneous asymmetric transformations is rarely achieved. In reactions which deracemize a single stereogenic center Pirkle et al, [15] Hoppe et al, [14] and Hoffmann et al [16] have achieved asymmetric induction approaching 80 % ee. Beak et al have achieved up to 98 % ee (at 10 % conversion) by using a limiting reagent to ªquenchº a homogeneous asymmetric transformation of an organolithium compound.…”
Section: Methodsmentioning
confidence: 98%
“…As the last example in equation 44 demonstrates, synthetically interesting enantioenrichments can be achieved from configurationally labile 1-phenylselanylalkyllithium compounds 140 . It has been shown that the e.r.…”
Section: Arsmentioning
confidence: 99%
“…It has been shown that the e.r. in aldehyde addition roughly corresponds with the d.r., and it has been concluded that the interconversion of diastereomers is slower than the addition step 140 .…”
Section: Arsmentioning
confidence: 99%